Molecular characterisation of XvVTC2, a gene coding for a GDP-L-galactose phosphorylase from Xerophyta viscosa - Bresler, Andries Petrus (Department of Molecular and Cell Biology, 2015)
Includes bibliographical references (leaves 100-108).